Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Mie Gacoan Merr Surabaya - Lasifau Maryamis; Iswati Iswati; Anis Fitriyasari; Arief Widijatmoko (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine the influence of product quality and price on purchasing decisions among Mie Gacoan Merr buyers in Surabaya this year. The method used in this research is a quantitative approach by distributing questionnaires to a sample of 75 respondents. The tool used for this research uses SPSS Version 25 with research instrument testing using data quality tests and classical assumptions, with the data analysis method used is multiple linear regression analysis. The results of this research show that (1) product quality has a partially positive and significant effect on purchasing decisions. (2) price has a partially positive and significant effect on purchasing decisions. (3) product quality and price simultaneously have a positive and significant effect on purchasing decisions with a percentage of 67%, and the remaining 33% is influenced by other variables outside this research.